Utilization of seaweed porridge Sargassum sp. and Eucheuma cottonii as cosmetic in protecting skin. (May 2019) - Nurjanah,; Luthfiyana, N; Hidayat, T; Nurilmala, M; Anwar, E
Abstract: UV radiation has negative effects on the health of the skin. The use of sunscreen everyday can absorb at least 85% sunlight at a wavelength of 290-320 nm. The purpose of this research was to find the best formulation of seaweed porridge Sargassum sp. and Eucheuma cottonii as a sunscreen cream qualified by antioxidant activity, SPF, physical evaluation of cream analysis and stability analysis. Cream formulation comprised of 5%, 6%, 7% and control. The best percentage of stocks from cream E. cottonii and Sargassum sp. were the cream preparation C. The value of antioxidant activity and SPF were 185±0.02 mg/mL and 2.1988, respectively. The pH value belongs to alkaline. Cycling test showed the cream preparation of the slurry E. cottonii and Sargassum sp. remained stable, there was no phase separation and discoloration. Centrifugal test results indicate that the cream has a shelf life for 1 year due to the absence of phase separation after given effect centrifugal force with a speed of 3, 800 rpm for 5 hours.